Poverty, Dickens’s Oliver Twist, and J. R. McCulloch - Ayşe Çelikkol (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
As the precursor to the science of economics, political economy concerned some topics that also preoccupied novelists, such as poverty and wealth. Literary criticism in the late twentieth and early twenty-first centuries has been charting the ways in which the discourses of literature and political economy intersect, despite the Romantic disavowal of their commonalities. Aiming to contribute to this ongoing scholarly effort, this essay pinpoints an unexpected affinity between Charles Dickens’s Oliver Twist, a novel which addresses the plight of the poor under the New Poor Law of 1834, and the political economist J. R. McCulloch’s writing on that piece of legislation. Both mistrust theoretical knowledge and privilege the particular as the basis on which one must make decisions. This affinity is unexpected because Oliver Twist repudiates political economy. Recognizing McCulloch’s and Dickens’s common epistemology alerts us to the ways in which the preference for the particular over the systemic shapes Oliver Twist. The common ground between Oliver Twist and McCulloch’s writing on the New Poor Law attests to the interconnectedness of literature and political economy.